The stylization of camouflage and seduction in the cover photos of the ads - Deconstructive semiotic approach - قوادر يعيشوش فاطمة زهراء, (International Journal of Social Communication, 2019)
The cover image is one of the important semanticthresholdsthat directs the reader to deduce the contents of Al-Matn and decipheritsfaults, withitspre-emptive and condensed indications of the contents of the subsequenttext, and its essence in itsownway. The problemwith the speech isthatthrough the adoption of a camouflage and seductionmechanism, and on top of that, it imposes on the recipient to arm themselveswith new mechanisms of interpretation,Anatomyrequires a kind of parallelbetweenwhatiscaligraphic and whatis formative, whichis a stylistic and semi-psychologicalsignthatisoftenat the beginning of the text, has an assignive and denotativefunction, and an influentialfunctionwhilereceiving the text, and itsacceptance and interaction, and fromthis perspective thispaper tries to try The research: An analysis of the cover of media advertisements in a semi-stylisticanalysis, in order to clarify the effect of concealed influence behindthese images, leading to the effect and satisfaction of the recipient.